2018
DOI: 10.14716/ijtech.v9i2.1031
|View full text |Cite
|
Sign up to set email alerts
|

CO2 Capture using Graphite Waste Composites and Ceria

Abstract: Solid sorbents based on graphite electrode waste and cerium oxide (ceria, CeO2) have been studied with regard to CO2 capture. The acid-base properties of cerium oxide produce a sorbent for the capture of CO2. The aim of the study is to evaluate the performance of CO2 capture using graphite/CeO2 composites at different weights of Ce(NO3)3.6H2O (0.5, 1 and 2 g), namely G0.5, G1 and G2, respectively. Volumetric adsorption studies of CO2 on graphite/CeO2 composites and ceria were conducted at various pressures (P)… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
5

Citation Types

0
10
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 34 publications
0
10
0
Order By: Relevance
“…The adsorption method, which is part of the carbon capture and storage (CCS) technology, is considered an efficient and economical method for replacing conventional technology in the CO2 scrubbing process, since the technology of amine solvents is deficient in corrosion and toxicity (Kartohardjono et al, 2017;Kusrini et al, 2018). Moreover, large amounts of energy are required to recycle amines, which diminishes the efficiency of energy usage, creates high costs in power plants, and produces corrosion in the pipeline (Ye et al, 2013;Mutyala et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…The adsorption method, which is part of the carbon capture and storage (CCS) technology, is considered an efficient and economical method for replacing conventional technology in the CO2 scrubbing process, since the technology of amine solvents is deficient in corrosion and toxicity (Kartohardjono et al, 2017;Kusrini et al, 2018). Moreover, large amounts of energy are required to recycle amines, which diminishes the efficiency of energy usage, creates high costs in power plants, and produces corrosion in the pipeline (Ye et al, 2013;Mutyala et al, 2019).…”
Section: Introductionmentioning
confidence: 99%
“…Sorption materials for wastewater treatment can be obtained from various production wastes. A vast variety of sorbents are produced from agricultural residues: sunflower husk, barley (Shaikhiev et al, 2010), wheat husk (Sobgaida et al, 2010), tea (Aslan et al, 2016), soybean and mustard (Humelnicu et al, 2015), leaf (Svyatchenko et al, 2020), peels (Kusrini et al, 2018), and others (Desmiarti et al, 2019;Olufemi and Eniodunm, 2018). The raw materials can be subjected to ultrasonic (Nasyrov et al, 2019) and heat treatment and exposed to acids and alkalis, thus obtaining materials with high sorptive properties at minimum costs (De Gisi et al, 2016).…”
Section: Introductionmentioning
confidence: 99%
“…To present, the reutilization of electrode graphite waste has only been as filler in the production of steel. To improve the use and value of this graphite waste, investigations for synthesis and characterization of graphite waste as valuable products, such as adsorbents (Kusrini et al, 2017;Kusrini et al, 2018) have been reported.…”
Section: Introductionmentioning
confidence: 99%